Peran Relawan Dalam Penanggulangan Bencana Erupsi Gunung Kelud - agus khoirul anam; Sri Winarni; Sylvia Rosi Andriani (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2017)
In the tackling of disaster is required the role of volunteer when disaster does not happen, ishappening, and after happened. The purpose of this research is to know the role of the indonesian red crossvolunteer in the tackling of Kelud eruption in Blitar. The population was all Indonesian Red Crossvolunteer in Blitar regency even Tenaga Sukarela (TSR) or Korps Sukarela (KSR) in 2016 as 150volunteer and the sample were taken as 30 people using Purposive Sampling. the result showed that 60%Indonesian Red Cross volunteer had enough role in tackling Mount Kelud eruption in Blitar Regency.The role of Indonesian Red Cross volunteer when not eruption is enough categorized as 50%, whenerupting is well categorized as 63,3% and pasca eruption is less categorized as 56,7%.